Comparing lunge techniques depending on the weapon used: Differences between foil and epee fencers - Dedieu, P.; Salesse, M.; Champain, G.; Zanone, P. (Journal of Physical Education and Sport, 2024)
Purpose: Despite different priority rules in epee and foil competitions, both weapons are trained using similar technical practices. This study aims to investigate whether these rule differences affect the coordination patterns observed in the lunge, a fundamental skill shared by both foil and epee fencers. Thus, we analyzed interlimb coordination between the leg and the arm on the fencers` armed side, as well as intergirdle coordination.